Analisis Yuridis terhadap Kewajiban Pemenuhan Hak Asasi Manusia dalam Praktik Bisnis Perkebunan Kelapa Sawit - Pardomuan Gultom; Rumainur Rumainur (Badan Strategi Kebijakan Hukum, 2022)
Human rights are natural rights inherent in every human being. In the classical human rights paradigm, the state is considered the main actor carrying out obligations to fulfill human rights as stated in the International Covenant on Civil and Political Rights (ICCPR) and the International Covenant on Economic, Social, and Cultural Rights (ICESCR). However, with the emergence of factsregarding the impact of the company's presence in a number of human rights violations, both domestic and multinational, there has been a discourse on the importance of non-state actors to be drawn as stakeholders in the human rights regime through the UNGP Principles in 2011. Agrarian conflicts as a result of the presence of oil palm plantations become a separate problem for business entities in the fulfillment of human rights, especially ESC rights, as a manifestation of the implementation of social and environmental responsibility norms. The method used in this research is normative legal research with a statute approach and a conceptual approach. This study aims to provide a juridical understanding that oil palm plantations as non-state actors also carry out obligations in fulfilling human rights.